2023
DOI: 10.1002/adfm.202213809
|View full text |Cite
|
Sign up to set email alerts
|

Switchable and Reversible p+/n+ Doping in 2D Semiconductors by Ionic 2D Minerals

Abstract: 2D semiconductors are promising for fabricating miniaturized and flexible electronic devices. The manipulation of polarities in 2D semiconductors is key to fabricate functional devices and circuits. However, the switchable and reversible control of polarity in 2D semiconductors is challenging due to their ultrathin body. Herein, a reversible and non‐destructive method is developed to dope 2D semiconductors by using ionic 2D minerals as the electrostatic gating. The 2D semiconductor channel can be reversibly tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…MFM phase and AFM topography were mapped and processed via Gwydion v2. 55 (an open source software for SPM analysis).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MFM phase and AFM topography were mapped and processed via Gwydion v2. 55 (an open source software for SPM analysis).…”
Section: Methodsmentioning
confidence: 99%
“…[49][50][51][52] Recently, mica group members started attracting attention as multifunctional insulators in 2D electronic applications, [42,53,54] and especially in novel memory concepts with 2D semiconductors. [55,56] As for the magnetic vdW minerals, the naturally occurring sulfosalt cylindrite with vdW superlattice was explored. [57] While it is possible to exfoliate monolayers, the bulk antiferromagnetic Néel temperature (T N ) was found to be below 20 K. [57] Furthermore, a recent study has demonstrated the possibility to exchange interlayer ions in micas and vermiculites and to fabricate twistronic superlattices, causing interlayer species to reorder accordingly with the twisting angle via the stacking method.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al reported the use of an ionic mica layer as top electrostatic gates to achieve reversible P/N transition. 11 Bu et al introduced a dual top-gated electrostatic doping method to regulate polarity. 12 Electrostatic doping avoids damage to the device, whereas additional gates increase the complexity of the process.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Doping is categorized into electrostatic, physical, and chemical doping processes. Zhang et al reported the use of an ionic mica layer as top electrostatic gates to achieve reversible P/N transition . Bu et al introduced a dual top-gated electrostatic doping method to regulate polarity .…”
Section: Introductionmentioning
confidence: 99%
“…There is no doubt that this will increase the redox reaction in the soil. As a result, it has received a lot of interest from academics, but the majority of them concentrate on the study of semiconductor mineral doping levels (Chen et al, 2021;Zhang et al, 2023) and pollution remediation (Tang et al, 2023). And there are few reports on how semiconductor minerals react to declining peatland water tables.…”
mentioning
confidence: 99%